History of the Biodiversity of Ladybirds (Coccinellidae) at the Black Sea Coast of the Russian Caucasus in the Last 120 Years—Does the Landscape Transformation and Establishment of Harmonia axyridis Have an Impact? - Bieńkowski, Andrzej O. (Insects, 2020)
SIMPLE SUMMARY: Studies of the history of regional insect fauna are important for understanding the changes in ecosystems and are therefore crucial for conservation decisions. The harlequin ladybird is a global invader that causes the decline of native ladybirds in some countries. Therefore, it is advisable to monitor the ladybird fauna in regions recently occupied by this species. We analyzed the dynamics of the fauna at the main sea resort of Russia over a period of 120 years to determine the following: (1) how the ladybird biodiversity changed during the intensive landscape transformation; (2) what alien species introduced for pest control have occurred to date; and (3) what the impact is of the harlequin ladybird on the ladybird fauna. We examined specimens collected by us and 54 other collectors including specimens from old museum collections and reconstructed the history of the biodiversity like a picture from puzzle pieces. Surprisingly, landscape transformation did not cause a decrease but rather an increase in ladybird biodiversity; most of the species recorded before 1930 have occurred to date, and 23 other species have spread to the region. Four released alien species occur in gardens and streets but not in natural habitats. The harlequin ladybird has been abundant for 10 years, but no ladybird species have disappeared in the region because of it. ABSTRACT: Studies of the history of regional insect fauna are important for understanding the changes in ecosystems. We analyzed the dynamics of ladybird fauna at the main sea resort of Russia over a period of 120 years to determine the following: (1) what species disappeared and what species appeared during landscape transformation; (2) what alien species introduced for pest control have been observed to date; and (3) whether the establishment of the global invader Harmonia axyridis (Coccinellidae) caused the extinction of some ladybird species in the Caucasus. We examined specimens collected by us and 54 other collectors including specimens from old museum collections and detected 62 species, 50 of which were collected in recent years (2011–2020). Landscape transformation and recreational use have caused not a decrease but an increase in ladybird biodiversity. Twenty-nine of 34 species recorded before 1930 have been observed in the region to date. Twenty-three other species have spontaneously spread to the region between 1930 and 2020 because of the creation of suitable anthropogenic habitats or because of unintentional introduction. Rodolia cardinalis, Cryptolaemus montrouzieri, Lindorus lophanthae, and Serangium montazerii were released for pest control, and they occur in gardens and streets but not in natural habitats. Harmonia axyridis, which appeared approximately 10 years ago, is abundant in urban and natural habitats, but there is no evidence that it caused the elimination of any ladybird species.